Efeito dos tratamentos térmicos e da severidade do entalhe na susceptibilidade à fragilização por hidrogênio do Inconel 718 avaliada pelo método de RSL - Souza, Danilo Eduardo Fonseca (2018)
Hydrogen, the smallest existing atom, can diffuse into the microstructure of materials, generating internal stresses and, through complex mechanisms, lead to premature fracture of structural components. This phenomenon affects the main groups of metal alloys used in the industry, from steels to niquel based corrosion-resistant alloys such as Inconel 718. The present study investigated the influence of ageing heat treatments on the microstructure and mechanical properties of the Inconel 718 superalloy, as well as the effect of notch roundness on the susceptibility to hydrogen embrittlement using the Rising Step Load (RSL) method, as predicted by ASTM F1624 standard. To determine the invariant threshold load (Pth), a method based on the difference between the test load and the predicted load (setpoint) was proposed for a given baseline load. Test coupons fabricated with notches with a 250 μm radius, as provided by ASTM F519 (ASTM, 2013) standard, were used as well as 80 μm, not standardized, in order increase the local stress concentration factor. Inconel 718 was subjected to two different heat treatments. In the first one, based on the API 6A CRA (2015) standard, which provides specifications for Inconel 718 use in subsea components, the solubilization was carried out at 1040 °C for 2 hours and the aging was done at 765 °C and 785 °C for 6 hours, obtaining microstructures with small platelets of δ phase at grain boundaries and hardness of 34 and 37 HRC, respectively. The second heat treatment was based on ASTM B637 (2015), solubilized at 1010 °C for 1 hour and aged at two sequential temperature levels of 718 °C for 8 hours and 621 °C for also 8 hours, a material with a hardness of 40 HRC and grain boundaries without noticeable amount of δ phase was obtained. Materials with a notch radius of 80 μm and δ phase in the grain boundaries were found more susceptible to hydrogen embrittlement when tested by the RSL method with a cathodic potential of -1.2 VAg / AgCl in 3.5 % aqueous NaCl solution compared to their peers with a radius of 250 μm.